Ela é carioca: um estudo da imagem da cidade do Rio de Janeiro sob o ponto de vista de cidadãos não-cariocas - Carneiro, Ana Paula de Souza (2007)
The study it was considered to carry through an analysis of the city of Rio de Janeiro using the point of view of not Carioca citizens - in this case Baianos and Paulistas. The optics chosen for the analysis was the image, that is the resultant of aspects such as: mental ideas, feelings, emotions, attitudes, thoughts, cognitions, expectations, representations, perceptions, certainties and associations. A research with qualitative focus was carried through, of exploratory character, with not Carioca individuals, Baianos and Paulistas, with and without experience in Rio de Janeiro. The results point the main reason of the visit - or not - to Rio de Janeiro, the symbol of the city, the perception concerning its image and about its inhabitant - the Carioca.